Board of Editor - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.- Papers must be a real work of the author.- Papers has never been published in other media.- Papers must contain discussion about Infrastructure & Facility Asset Management.- Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.- The paper has to take references from Scientific Journal with minimum of 5 papers.- Paper lengths are limited in 8-16 pages.- Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of the following.- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Policy- I & F Planning- I & F Administration Aspects- I & F Operation System- I & F Maintenance System- I & F Evaluation Technique- I & F Disposal- I & F Economical Aspect- I & F Financial Aspect- I & F Management Organization- I & F Spatial Aspects and Environmental Aspects